ChemInform Abstract: Rh(II)/Broensted Acid Cocatalyzed Intramolecular Trapping of Ammonium Ylides with Enones: Diastereoselective Synthesis of 2, 2, 3‐Trisubstituted Indolines. Issue 10 (March 2015) - Jiang, Liqin; Xu, Renqi; Kang, Zhenghui; Feng, Yixiao; Sun, Fengxia; Hu, Wenhao
Abstract The described procedure gives access to a large variety of the title compound class in moderate to good yields with excellent diastereoselectivities.